Social Relations in Clove and Rubber Plantations - Gunawan, Gunawan; Sholeh, Muh; Nastiti, Tur; Nathalia, Elsha Pipit; Kartika, Ema (Universitas Negeri Semarang, 2024)
Plantations are a vital non-oil and gas sector that contributes to state revenues. However, the potential of plantations in Indonesia has not fully provided welfare for planters due to the complexity of social networks in management and harvesting. This article attempts to describe how social networks are formed in rubber and clove plantations by looking at the context of social structures in society. The focus of the Research on rubber and clove plantations is not to make comparisons but to explore more broadly the forms of social relations in different plantation management systems and commodity types. Data were collected through a qualitative approach using direct observations and interviews with rubber tappers and clove planters. The study results indicate that in managing rubber latex, tappers use sales networks with companies and middlemen, while in clove plantations, harvesting is closely related to the social relations of the community. This situation indicates that the management system and commodity type determine the social ties formed.